Dampak Psikologis Tokoh Pria dan Wanita dalam Film Tangshan Da Dizhen - Andriani Sinarsih; Yuvina Handani; Cendrawaty Tjong (Lingua Cultura, 2015)
"Tangshan Earthquake" by Feng Xiaogang began shooting at the 2010 Aftershock of a background to the film. Movie tells the story of a mother for her daughter because of the expense of her choice between life and death caused deep trauma, the purpose of this study was to indicate the difference between sex behavior may cause deep psychological trauma. This article uses the collected literature research method, to "Aftershock" movie LiYuanni Stool and post-disaster psychological research scope and use of gender inequality theory, post-disaster trauma psychology to analyze the process of gender inequality in the movie protagonist psychology. Analysis showed that factors of gender inequality is mainly a social problem and a lack of self-consciousness of women. The uneven treatment of choice in pondering Fang Deng and mother for decades.